Influence of waste paper and wheat straw on the growth of the oyster mushroom Pleurotus sajor kaju with additional nutrients : - - Mistry, Dr.Sneha jayanitibhai (Mushroom Research, 2023)
Mushroom cultivation is an economically feasible bio-technological process for conversion of various lignocellulosic wastes. This study was conducted at Department of Plant Pathology with the aim of evaluating the suitability of waste paper supplemented with wheat straw and wheat bran for Oyster mushroom cultivation. Therefore, an experiment with different concentration of waste paper supplemented with wheat straw and wheat bran were tested for their productivity and biological efficiency (BE) for cultivation of Pluerotus sajor kaju mushroom. Higher total yield (949.20 gm) and BE (94.92%) were obtained from waste paper (50%) + wheat straw (25%) +wheat bran (25%). However, Lower (56.82%) BE were obtained from waste paper (100%). This study revealed that waste paper supplemented with wheat straw and wheat bran results in high BE and total yield. Thus, appears to be a promising alternative for the cultivation of oyster mushroom. Yet, waste paper without supplement poorly supports the growth of oyster mushroom.